After the crisis? Big Data and the methodological challenges of empirical sociology. Issue 1 (10th July 2014) - Burrows, Roger; Savage, Mike
Google Trends reveals that at the time we were writing our article on 'The Coming Crisis of Empirical Sociology' in 2007 almost nobody was searching the internet for 'Big Data'. It was only towards the very end of 2010 that the term began to register, just ahead of an explosion of interest from 2011 onwards. In this commentary we take the opportunity to reflect back on the claims we made in that original paper in light of more recent discussions about the social scientific implications of the inundation of digital data. Did our paper, with its emphasis on the emergence of, what we termed, 'social transactional data' and 'digital byproduct data' prefigure contemporary debates that now form the basis and rationale for this excellent new journal? Or was the paper more concerned with broader methodological, theoretical and political debates that have somehow been lost in all of the loud babble that has come to surround Big Data. Using recent work on the BBC Great British Class Survey as an example this brief paper offers a reflexive and critical reflection on what has become – much to the surprise of its authors – one of the most cited papers in the discipline of sociology in the last decade.